1988
DOI: 10.1063/1.341237
|View full text |Cite
|
Sign up to set email alerts
|

Silicon oxynitride films: Ion bombardment effects, depth profiles, and ionic polarization, studied with the aid of the Auger parameter

Abstract: Thin films of Si3 N4, SiO2, and of silicon oxynitrides with compositions in the range 0.3≤O/N≤3.6 were deposited on silicon substrates to thicknesses between 20 and 150 nm by low-pressure chemical vapor deposition. Auger parameters of the films were measured during the study of ion bombardment effects and depth profiling, and as a function of the O/N ratios. The particular parameter used was based on the Si 2s photoelectron, and bremsstrahlung-excited Si KLL Auger lines. When normalized to const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…In particular, when E Ar C ¾ 1-4 keV, the Si-Si bonding states appear to be confined chiefly at the outermost layers of the sample, because Si LVV spectra (electron inelastic mean free path ¾ 0.4 nm) 4 show a damage component at KE ¾ 92 eV, whereas the more 'bulksensitive' Si KLL transition ( ¾ 3 nm) 4 remains virtually unaffected. 3 (Similar conclusions also were drawn by this author in considering the synchrotron radiation photoemission Si 2p spectra of Ar C -etched silica surfaces carried out at the same surface sensitivity as that of Si LVV spectra.) 5 As a consequence, it has been recommended that use of the Si LVV line, both as a chemical indicator and as a measure of silicon concentration, should be avoided in the Auger analysis of such Ar Cetched materials.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In particular, when E Ar C ¾ 1-4 keV, the Si-Si bonding states appear to be confined chiefly at the outermost layers of the sample, because Si LVV spectra (electron inelastic mean free path ¾ 0.4 nm) 4 show a damage component at KE ¾ 92 eV, whereas the more 'bulksensitive' Si KLL transition ( ¾ 3 nm) 4 remains virtually unaffected. 3 (Similar conclusions also were drawn by this author in considering the synchrotron radiation photoemission Si 2p spectra of Ar C -etched silica surfaces carried out at the same surface sensitivity as that of Si LVV spectra.) 5 As a consequence, it has been recommended that use of the Si LVV line, both as a chemical indicator and as a measure of silicon concentration, should be avoided in the Auger analysis of such Ar Cetched materials.…”
supporting
confidence: 72%
“…E-mail: paparazzo@ism.rm.cnr.it successful in avoiding surface charging phenomena, it should be remembered that Ar C ions are quite likely to produce artefacts. Indeed, there is ample evidence in the literature 3 that Ar C ions produce silicon reduction as a result of preferential removal of nitrogen or oxygen in silicon nitrides, silicon oxynitrides and silica. In particular, when E Ar C ¾ 1-4 keV, the Si-Si bonding states appear to be confined chiefly at the outermost layers of the sample, because Si LVV spectra (electron inelastic mean free path ¾ 0.4 nm) 4 show a damage component at KE ¾ 92 eV, whereas the more 'bulksensitive' Si KLL transition ( ¾ 3 nm) 4 remains virtually unaffected.…”
mentioning
confidence: 98%
“…Although the quantitative analytical data were derived from the peak integrals, a nonlinear correlation between composition and Auger intensity was observed in [34], similar to [97]. The spectra show the decomposition of the oxygen-rich AlO X N Y film.…”
Section: S Dreer and P Wilhartitzmentioning
confidence: 99%
“…In [126], the authors concluded from the AES spectra that oxygen and nitrogen were mixed on an atomic scale in the oxynitride films, not forming a mixture of SiO 4 and Si 3 N 4 tetrahedra. This work was also mentioned in [97], where the authors indicate the problems of the investigations, such as specimen charging, electron beam-induced damage and sample decomposition, the inherent high, sloping, inelastic background, etc. The authors of this publication thus prefer XPS.…”
Section: S Dreer and P Wilhartitzmentioning
confidence: 99%
See 1 more Smart Citation